1996
DOI: 10.1002/(sici)1097-4628(19961121)62:8<1205::aid-app10>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

The anhydride content of some commercial PP-g-MA: FTIR and titration

Abstract: SYNOPSISA set of anhydride-grafted polypropylenes was collected from various companies. They were studied in light of our recent results on polypropylene melt grafted with maleic anhydride.' This work confirmed that an important decrease of the anhydride content is recorded on heating or washing, due to the elimination of free, ungrafted products, respectively, by sublimation of maleic anhydride and by polymaleic anhydride solubilization. The deconvolution of the infrared spectra of washed anhydride-grafted po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 1 publication
4
61
1
2
Order By: Relevance
“…In similar studies using PP, they also confirmed that the grafts exist as either single saturated units or unsaturated grafts consisting of an anhydride ring attached to the chain terminus via a double bond. This was contrary to the conclusions by Scalvons et al 7 who, using FTIR, suggested the formation of oligomeric and polymeric grafts. In the present work using 1% MAn in TMCH, only single saturated grafts are found.…”
Section: Nature Of the Graftscontrasting
confidence: 93%
See 1 more Smart Citation
“…In similar studies using PP, they also confirmed that the grafts exist as either single saturated units or unsaturated grafts consisting of an anhydride ring attached to the chain terminus via a double bond. This was contrary to the conclusions by Scalvons et al 7 who, using FTIR, suggested the formation of oligomeric and polymeric grafts. In the present work using 1% MAn in TMCH, only single saturated grafts are found.…”
Section: Nature Of the Graftscontrasting
confidence: 93%
“…In these latter studies, FTIR was used to characterize the graftmodified polymer and to distinguish the single grafts from oligomeric grafts and free homopolymer. In a subsequent study, 7 commercial samples of grafted polyolefin were analyzed and similar conclusions were reached. The results from FTIR were not confirmed using other techniques such as NMR.…”
Section: Introductionmentioning
confidence: 60%
“…The polypropylene (PP) was purchased from Panjin Chemical Factory; the Nylon 6 (PA6) was purchased from Allied Signal Corporation and dehumidified by using a vacuum oven at 80 0 C for 24 h before blending; the PP-g-DBM was synthesized by melt grafting in the presence of dicumyl peroxide (DCP) using twin screw extruder in our laboratory, percent grafting of PP-g-DBM was measured by chemical analysis [20].…”
Section: Methodsmentioning
confidence: 99%
“…Grafting of MA or other polar monomers onto NR backbone improves the compatibility between NR and other polar elastomers and some engineering plastics such as polyamide. According to several authors [53][54][55][56][57][58][59], the grafting process of MA onto polydienes, such as NR, styrene-isoprene, and styrene-butadiene-styrene block copolymer, involves two different mechanisms, i.e., radical-induced grafting and thermal grafting via an ene mechanism. For the ene mechanism, high temperature (160-240°C) is required for the fixation of MA to polydiene backbone.…”
Section: Recent Progress In Rubber-organoclay Nanocompositesmentioning
confidence: 99%